A modified PV-wind-PEMFCS-based hybrid UPQC system with combined DVR/STATCOM operation by harmonic compensation. (4th July 2021) - Sarker, Krishna; Chatterjee, Debashis; Goswami, S. K.
ABSTRACT: This paper describes an improved Flexible Alternating Current Transmission System (FACTS)-based custom power controller with dynamic voltage restorer (DVR), static compensator (STATCOM) and unified power quality conditioner (UPQC) topology. The proposed controller can feed the power to grid and proficiently moderate the power quality problems like sag, swell, flicker, voltage interruption, reactive and active power compensation and voltage disturbances with harmonic problems to make sure power quality in the distribution system. The proposed configuration utilizes the Distributed generations (DGs), e.g. Photovoltaic (PV), wind and proton exchange membrane fuel cell stack connected to the micro-grid for realilazisation of DVR, STATCOM and UPQC operation with reduced filtering requirements. Space vector pulse width modulation -based hybrid cascade bottom leg multilevel inverter has been used for this purpose. The proposed topology has been simulated using MATLAB/Simulink and validated experimentally on a practical system. It is shown that the UPQC performs significantly better than the DVR and STATCOM for the improvement of different power quality issues.